HIVIS-DNA or HIVISopt-DNA priming followed by CMDR vaccinia-based boosts induce both humoral and cellular murine immune responses to HIV. Issue 6 (June 2017) - Hinkula, J; Petkov, S; Ljungberg, K; Hallengärd, D; Bråve, A; Isaguliants, M; Falkeborn, T; Sharma, S; Liakina, V; Robb, M; Eller, M; Moss, B; et al.
Abstract: Background: In order to develop a more effective prophylactic HIV-1 vaccine it is important optimize the components, improve Envelope glycoprotein immunogenicity as well as to explore prime-boost immunization schedules. It is also valuable to include several HIV-1 subtype antigens representing the world-wide epidemic. Methods: HIVIS-DNA plasmids which include Env genes of subtypes A, B and C together with Gag subtypes A and B and RTmut/Rev of subtype B were modified as follows: the Envelope sequences were shortened, codon optimized, provided with an FT4 sequence and an immunodominant region mutated. The reverse transcriptase (RT) gene was shortened to contain the most immunogenic N-terminal fragment and fused with an inactivated viral protease vPR gene. HIVISopt-DNA thus contains fewer plasmids but additional PR epitopes compared to the native HIVIS-DNA. DNA components were delivered intradermally to young Balb/c mice once, using a needle-free Biojector® immediately followed by dermal electroporation. Vaccinia-based MVA-CMDR boosts including Env gene E and Gag-RT genes A were delivered intramuscularly by needle, once or twice. Results: Both HIVIS-DNA and HIVISopt-DNA primed humoral and cell mediated responses well. When boosted with heterologous MVA-CMDR (subtypes A and E) virus inhibitory neutralizing antibodies were obtained to HIV-1 subtypes A, B, C and AE. Both plasmid compositions boosted with MVA-CMDR generated HIV-1 specific cellular responses directed against HIV-1 Env, Gag and Pol, as measured by IFNγ ELISpot. It was shown that DNA priming augmented the vector MVA immunological boosting effects, the HIVISopt-DNA with a trend to improved (Env) neutralization, the HIVIS-DNA with a trend to better (Gag) cell mediated immune reponses. Conclusions: HIVIS-DNA was modified to obtain HIVISopt-DNA that had fewer plasmids, and additional epitopes. Even with one DNA prime followed by two MVA-CMDR boosts, humoral and cell-mediated immune responses were readily induced by priming with either DNA construct composition. Priming by HIV-DNA augmented neutralizing antibody responses revealed by boosting with the vaccinia-based heterologous sequences. Cellular and antibody responses covered selected strains representing HIV-1 subtypes A, B, C and CRF01_AE. We assume this is related to the inclusion of heterologous full genes in the vaccine schedule.